1988
DOI: 10.1099/00222615-25-3-175
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between haemagglutination and adherence to epithelial cells in Yersinia pseudotuberculosis

Abstract: Summary. Yersinia pseudotuberculosis was examined for its haemagglutinating activity and adherence to cultured epithelial cells (HEp-2) in relation to possession of a virulence (VW) plasmid and to growth conditions. VW-lacking (VW -) bacteria were isolated from ten VW' strains of each serovar which, after they were grown on CFA plates at 37"C, agglutinated the erythrocytes from five different species. In contrast to the bacteria possessing the plasmid (VW') half of the VW-bacteria, grown on CFA plates at 37"C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Most previous publications dealing with the adhesive properties of Yersiniue have studied the interaction between these bacteria and various epithelial cell lines (e.g. 5 , 12,13,17,19,22,26,28). In one study, strains of the Y. enterocoliticu pathogenic serotypes 0:3, 0:8 and 0:9 adhered to and invaded enterocytes of human fetal gut (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous publications dealing with the adhesive properties of Yersiniue have studied the interaction between these bacteria and various epithelial cell lines (e.g. 5 , 12,13,17,19,22,26,28). In one study, strains of the Y. enterocoliticu pathogenic serotypes 0:3, 0:8 and 0:9 adhered to and invaded enterocytes of human fetal gut (4).…”
Section: Discussionmentioning
confidence: 99%
“…Two chromosomal loci, which code for invasion of epithelial cells, have recently been identified (24). However, other investigations have provided evidence that both chromosomal and plasmid genes may be involved in the adhesion process (12,13,17,26).…”
Section: Discussionmentioning
confidence: 99%
“…Kawaoka et al (14) reported that Y. pseudotuberculosis strains isolated from various mammalian species including human, monkey, pig, dog, rabbit, guinea pig, rat, duck and pigeon, produced HA in the culture medium and that the HA productivity of the yersinial strain was unrelated to the binding ability of it to mammalian epithelial cells. An essential step in infections caused by enteroinvasive bacteria is the penetration of intestinal cells (5,12,22,25).InY.pseudotuberculosis a single chromosomal gene (inv) that encodes a 103-kilodalton protein (invasin) is sufficient to confer an invasive character on noninvasive E. coli HB101 (10,11,15).…”
Section: Purification Of the Hamentioning
confidence: 99%
“…It seems likely that the relationships between HA, plasmid, invasion and adherence differ from case to case. The hemagglutinin in pathogenic Y. enterocolitica (15) expressed on the cell surface of VW+ bacteria grown at 37 C was considered to confer hydrophobic property on the cells, while the HA produced by Y. pseudotuberculosis grown at 37 C did not confer hydrophobicity to the cells (14). Each of the HAs purified from the strains R148R and TP1040 appeared to be composed of a single protein with a molecular weight of 14,000 to 15,000, which were virtually identical to that of the HA previously purified from the strain Inoue (29).…”
Section: Purification Of the Hamentioning
confidence: 99%
See 1 more Smart Citation